Participação dos neurônios noradrenérgicos do locus coeruleus nas manifestações comportamentais e respiratórias ao ataque de pânico induzido por CO2 - Ripamonte, Gabriel Carvalho (2022)
It is well described that imbalances in the modulation of locus coeruleus norepinephrine (LC-NA) neurotransmission are responsible for several psychiatric disorders, including panic disorder. Patients with such a disorder are more sensitive to changes in CO2/pH and therefore are more likely to experience the "suffocation false alarm" which, in turn, triggers the panic attack. LC-NA neurons are involved in ventilatory responses to moderate concentrations of CO2/pH; however, its involvement in behavioral and respiratory responses to severe acidification is still unknown. We investigated the participation of LC-NA neurons by using C56BL/6 mice with a conditional knockout allele of Dbh (DbhcKO) crossed with En1cre (En1CreDbhcKO - LC-NA mutants). In addition, an hypomorphic genotype animal of the same genetic background was used (En1wtDbhcKO) as well as control animals (En1wtDbhwt) of both sexes (10-12 weeks; 20-25 g). The animals went through a period of habituation in ambient air, followed by exposure to normocapnic air (15 min) and then a mixture of gases enriched with 20% CO2 (7 min). The respiratory and metabolic response were VT, fR, VE, VO2 and VE/VO2 to each exposure. The behavioral responses analyzed were escape (jumping/running) and time spent immobile (freezing). In addition, the monoaminergic concentration in the brainstem and forebrain was investigated. A neuroanatomical study to determine which region of the LC communicates with the central nucleus of the amygdaloid complex (CA) and rostral ventrolateral medulla oblonga (RVLM), respectively responsible for fear and anxiety-like behavior and respiratory responses. In these regions, retrobeads were injected and the point of interest was evaluated. In addition, regions in which were activated in LC by 0 and 20% CO2 concentration were also analysed by c-Fos protein immunolocalization. The experimental protocols were approved by the local ethics committee (CEUA - n° 3340/20). LC-NA male mutant and hypomorphic rodents had a hypoventilation and a lower VE/VO2 compared to the control group. Furthermore, control male animals had a higher respiratory frequency then the same female group. LC-NA male mutant mice had a blunted jumping response (P=0.001) and more time spent in freezing (P<0.0001) compared to the other groups. Furthermore, LC-NA mutant animals had fewer racing episodes (P=0.0157) compared to wild animals. The En1wtDbhcKO group also presented a small number of jumps (P= 0.03913). No sex difference was observed among groups. In the brainstem, mutant males have a lower NA concentration than the control group (P= 0.03647). Furthermore, control males have a higher concentration of NA than females from the same group (P= 0.018141). Mutant females have a higher concentration of DOPAC than control females (P=0.003755). In the forebrain, mutant and hypomorphic animals of both sexes had a lower amount of NA compared to controls. The CA/LC projections seem to connect mainly neurons from the caudal and the dorsal medial-caudal region, while the RVLM/LC communication occurs throughout the locus coeruleus extension. Interestingly, most of the neuronal activation occurs in the caudal medial region of the LC in males, besides to the rostral medial and rostral regions, which does not occur in females. These findings suggest that norepinephrine originating from the LC has an important role in the respiratory and panic-like escape responses elicited in mice by exposure to CO2 in a sex independent way, despite being more prominent in males.